Granito morrinhos – magmatismo da Suíte Intrusiva Pensamiento – tereno paraguá – sudoeste do Cráton Amazônico - França, Ohana (2014)
This work presents the geologic, petrological, and geochronological data of Morrinhos Granite belonging to Pensamiento Intrusive Suite, located in the areas of Paraguá Terrain, southwestern portion of the Amazonian Craton. Geological mapping allowed the identification of two facies in Morrinhos Granite, which are: Hornblende-biotite granodiorite e Biotite monzogranite, the first of which predominates in areal extent. The first facies is characterized by leucocratic rocks, light gray, consisting of quartz, plagioclase, alkali feldspar, biotite and hornblende, unlike facies Biotite monzogranite, that is consisting of pinkish gray leucocratic rocks, with biotite as the only mafic essential. Both metamorphosed at greenschist facies. Chemically, these rock types characterize an acid sequence formed by sub alkaline magmatism, alkali-calcic metaluminous to slightly peraluminous type with some features A-type granites as standard evolved through fractional crystallization mechanisms. Structural data show two phases of deformation represented by the schistosity (S1) and cleavage crenulation (S2) with preferential attitude, respectively, 220 /80 and 350/85, both probably related to San Ignácio Orogeny. Geochronological determination obtained by the U-Pb (SHRIMP) and isotope geochemistry (Sm-Nd) of these rocks indicate, respectively, crystallization age 1350 ± 12 Ma, TDM around 1.77 Ga and negative value for εNd(1.35) of -2.57.The results obtained suggest that the Morrinhos Granite has been generated in a continental magmatic arc during the post colisional stage of San Ignacio Orogeny and allow to recognizes as an extension of Pensamiento Intrusive Suite.